GROUNDING CHURCH Initiative: Church's Initiative To Develop Environmental Awareness - Musdodi Frans Jaswin Manalu (Universitas Sanata Dharma, 2023)
This research explores the various activities that churches can undertake to encourage their congregations to be more concerned about environmental damage. The case study focuses on PT Toba Pulp Lestari in Porsea, North Sumatra. Despite its benefits in driving the community’s economy, many cases of environmental damage have occurred due to the establishment of this mill since its inception. At the same time, there have been protests, demonstrations, and anarchist actions, some ofwhich have been supported by the local Church aimed at closing the mill. I believe the Church should not resort to such violent acts, but I also disagree that the Church has not taken any initiative to minimize the damage. The reason for the Church to participate in saving the environment is so that the Church does not get caught up in the theoretical understanding that is only centered on teaching in the Church room, thus forgetting the practice taught in daily life. This paper provides various initiatives the Church can take to encourage its people to be actively involved and care more about the environment.